The role of Anatolia between Asia and Europe: A case study of oak gall wasp species, Cynips quercus (Hymenoptera, Cynipidae) - Serdar Dinç; Serap Mutun (Journal of Advanced Research in Natural and Applied Sciences)
In this study, we used DNA sequence data of a western Palearctic oak gall wasp species, Cynips quercus, showing distribution from Europe to Iran to answer the following questions: i) Do the eastern C. quercus populations have higher genetic diversity than the European populations?, ii) Are the eastern populations source for the European populations?, iii) What is the possible date of divergence between the Asian and European populations? For these purposes, we analysed 88 cytochrome b sequences representing Iran, Türkiye, Hungary, and Spain. Our analyses revealed that the highest genetic diversity was in Türkiye followed by Iran, Hungary, and Spain, respectively. Iranian samples were most divergent from the Spain and Hungary sequences. Pairwise comparisons showed that the highest gene flow was between Türkiye and Hungary, and between Türkiye and Iran, respectively. Phylogenetic analysis grouped the Turkish haplotypes with the Iranian sequences, and Spain was grouped with Hungary. Network analysis revealed that the western Turkish samples were separated from eastern sequences, and all of the eastern Turkish sequences were clustered with the Iranian samples meanwhile a western Turkish lineage provided a source to Hungary and then to Spain. Times of divergence analysis estimated that the Turkish lineage split from the Iranian lineage around 4,67 million years ago, and Hungarian and Spanish lineages diverged from each other about 3 million years ago. Correspondingly, our analyses suggested that Anatolia played a key role as a bridge between the Asian and European populations of C. quercus.